PENGARUH WAKTU PENUNDAAN PENGOLAHAN BUAH SAWIT Elaeis guineensis TERHADAP MUTU CRUDE PALM OIL DENGAN ALAT PENGOLAHAN SAWIT TIPE BATCH - Ivoni Susanti; Fitria Lestari (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to Analyze the effect of time delay on processing of palm fruit from Elaeis guineensis Jacq to Crude Palm Oil (CPO) quality. Fresh fruit marks are chopped to separate with fruit marks in the form of brondolan, then separated between inside and outside fruit and then treated with processing delays 0 hours, 6 hours, 12 hours, 18 hours and 24 hours. Further processed by using Batch type palm oil processing tool. CPO is analyzed CPO quality which consist of free fatty acid test, water content test and dirt level test. From result of measurement and quality test show the effect of time delay of processing of palm fruit to increase free fatty acid especially at treatment delay for 24 hours on fruit palm inside. The result of comparison of CPO quality measurement (ALB level, moisture content and dirt level) is still far below SNI standard.